Congenital distichiasis: a condition difficult to be treated - Santos, Caio Costa [UNESP]; de Almeida, Alice Carvalho Gouveia [UNESP]; Andrade, Alisson Lima [UNESP]; Schellini, Silvana Artioli [UNESP]; de Sousa Meneghim, Roberta Lilian Fernandes [UNESP] (Revista Brasileira de Oftalmologia, 2024)
Congenital distichiasis is a rare condition, of controversial origin, with therapeutic options not always having favorable results. This is a case report of a seven-year-old male child with congenital distichiasis affecting all eyelids, with the presence of some distichiasis hair follicles despite surgical treatment using the interlamellar division technique, selective application of cryotherapy and electrolysis. The treatment of congenital distichiasis involves the need to combine techniques to achieve more effective results.
Distiquíase congênita: uma afecção de difícil tratamento
Keywords: Child; Congenital distichiasis; Criança; Crioterapia; Cryotherapy; Cílio; Distiquíase congênita; Electrolysis; Eletrólise; Eyelashes; Eyelids; Pálpebras